2014
DOI: 10.1016/j.conb.2014.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling competence and transcriptional hierarchies with stochasticity in retinal lineages

Abstract: HighlightsProblems with a strict retinal competence model are explained.The apparent conflict between transcriptional hierarchies and stochasticity is resolved.The underlying nature of retinal progenitor cell stochasticity is discussed.Key issues that can be addressed in the face of stochasticity are enumerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 54 publications
4
51
0
Order By: Relevance
“…Next, we tested the expression of key retinal developmental genes, specific to particular cell types. Atoh7, Islet1, and Onecut2 are expressed early in retinal neurogenesis and are important for generation of retinal ganglion cells and other early‐generated cell types, whereas Otx2 is necessary for photoreceptors and bipolar cells (Boije et al, ). Ascl1 transduction resulted in a significant upregulation of all of these genes, in accordance to our previous study (Pollak et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we tested the expression of key retinal developmental genes, specific to particular cell types. Atoh7, Islet1, and Onecut2 are expressed early in retinal neurogenesis and are important for generation of retinal ganglion cells and other early‐generated cell types, whereas Otx2 is necessary for photoreceptors and bipolar cells (Boije et al, ). Ascl1 transduction resulted in a significant upregulation of all of these genes, in accordance to our previous study (Pollak et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore ATOH7 expressing progenitors do not exclusively develop into RGCs, as lineage tracing of ATOH7+ cells revealed that many ATOH7+ cells become amacrine cells, horizontal cells, and rod and cone photoreceptors (Brzezinski et al, 2012; Feng et al, 2010). Thus, it will be interesting in future studies to understand the nature of all the cells in the CD184hi population especially given the heterogeneous character of RPCs and probabilistic decisions associated with RPC cell fate commitment (Boije et al, 2014; Cepko, 2014; Kiyama et al, 2011; Trimarchi et al, 2008). The CD184hi CD171+ fraction showed variable enrichment of transcripts for inner neurons ( TFAB2B, PTF1A, LIM1, PROX1 ) and photoreceptors ( CRX ) suggesting that photoreceptors, horizontal and amacrine cells can be present (Figures 5G and S5).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, Boije et al () emphasize stochasticity, in the sense that all fates are available to all cells at any one time. We stress, however, that even though each individual cell might stochastically differentiate into one of the limited fates available, there are strong signs of tight regulation of the differentiation process, with most cell sub‐types involved in the control of their temporal restriction.…”
Section: Similarities and Differences Between Homeostatic And Developmentioning
confidence: 99%